2021
DOI: 10.3389/fevo.2021.624451
|View full text |Cite
|
Sign up to set email alerts
|

Global Connectivity of Southern Ocean Ecosystems

Abstract: Southern Ocean ecosystems are globally important. Processes in the Antarctic atmosphere, cryosphere, and the Southern Ocean directly influence global atmospheric and oceanic systems. Southern Ocean biogeochemistry has also been shown to have global importance. In contrast, ocean ecological processes are often seen as largely separate from the rest of the global system. In this paper, we consider the degree of ecological connectivity at different trophic levels, linking Southern Ocean ecosystems with the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 337 publications
(494 reference statements)
2
28
0
Order By: Relevance
“…Although ocean basin connectivity is rather high at the scale of our study (Jönsson & Watson, 2016), dispersal by marine currents and mesoscale processes are known to impact plankton community structure (Richter et al, 2020; Sommeria-Klein et al, 2021). For instance, the Antarctic Polar Front seems to be the main delimiter between regions 3 and 4, which coincides with the view that it imposes a strong physical barrier on passively drifting zooplankton (Murphy et al, 2021). Yet, recent evidence showed that many epipelagic plankton can cross Southern Ocean fronts thanks to the very dynamic meandering eddies (Murphy et al, 2021), which could explain the deviations of the region 4 boundaries from the Antarctic Polar Front.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although ocean basin connectivity is rather high at the scale of our study (Jönsson & Watson, 2016), dispersal by marine currents and mesoscale processes are known to impact plankton community structure (Richter et al, 2020; Sommeria-Klein et al, 2021). For instance, the Antarctic Polar Front seems to be the main delimiter between regions 3 and 4, which coincides with the view that it imposes a strong physical barrier on passively drifting zooplankton (Murphy et al, 2021). Yet, recent evidence showed that many epipelagic plankton can cross Southern Ocean fronts thanks to the very dynamic meandering eddies (Murphy et al, 2021), which could explain the deviations of the region 4 boundaries from the Antarctic Polar Front.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, the Antarctic Polar Front seems to be the main delimiter between regions 3 and 4, which coincides with the view that it imposes a strong physical barrier on passively drifting zooplankton (Murphy et al, 2021). Yet, recent evidence showed that many epipelagic plankton can cross Southern Ocean fronts thanks to the very dynamic meandering eddies (Murphy et al, 2021), which could explain the deviations of the region 4 boundaries from the Antarctic Polar Front. Therefore, the gradient in community trait expression separating regions 3 and 4 may also stem from the latitudinal gradient in temperature and biogeochemical conditions that select species and their traits based on physiological and metabolic constraints.…”
Section: Discussionsupporting
confidence: 79%
“…Managing greenhouse gas emissions is the primary way that these changes in the Earth System can be moderated (IPCC, 2018). Changes in polar regions impact people the world over, not just from the perspective of physics and tangible services from within the region (Meredith et al, 2019;Cavanagh et al, 2021) but also from more distant biological and human connections with the regions (Murphy et al, 2021;Roberts et al, 2021). Adaptation may attenuate impacts of climate change to socioecological systems in the near term (see Simpson et al, 2021) but cannot protect the fundamental nature of cold-and icedependent marine ecosystems, which are projected to experience rapid and irreversible loss over the next century under high (and possibly moderate) emission scenarios.…”
Section: Policy Relevant Climate Assessmentsmentioning
confidence: 99%
“…In addition to the perturbations that have already impacted the Southern Ocean, major changes in its habitats and ecosystems are expected over the coming years in response to increased pressures from a range of global (see Morley et al, 2020) and local environmental drivers (see Grant et al, 2021), the majority of which have an anthropogenic component (Murphy et al, 2007b;Rogers et al, 2007;Clarke et al, 2012;Constable et al, 2014b;Gutt et al, 2015;Chown and Brooks, 2019;Kennicutt et al, 2019). Owing to the extensive physical, biogeochemical, and ecological connectivity between Southern Ocean ecosystems and the global ocean, future changes in the structure and functioning of these ecosystems will also have consequences throughout the Earth System (Henley et al, 2020;Murphy et al, 2021). To predict how Southern Ocean ecosystems will respond to global change and the implications for regional and Earth System functioning and decision-making, assessments of the sensitivity of Southern Ocean zooplankton to changes in these drivers are necessary (Constable et al, 2014a,b).…”
Section: Introductionmentioning
confidence: 99%